Handbook of meat, poultry and seafood quality - Nollet, Leo M. L. , 1948-
The second edition of Handbook of Meat, Poultry and Seafood Quality, focuses exclusively on quality aspects of products of animal origin, in depth discussions and recent developments in beef, pork, poultry, and seafood quality, updated sensory evaluation of different meat products, revised microbiological aspects of different meat products